The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12864-022-08851-8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopancreas transcriptome analyses provide new insights into the molecular regulatory mechanism of fast ovary maturation in Macrobrachium nipponense

Abstract: Background Macrobrachium nipponense is an economically and ecologically important freshwater prawn that is widely farmed in China. In contrast to other species of marine shrimp, M. nipponense has a short sexual maturity period, resulting in not only high stocking densities, but also a reduced survival rate and increased risk of hypoxia. Therefore, there is an urgent need to study the molecular mechanisms underlying fast ovary maturation in this species. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Vtg1 is expressed primarily in the hepatopancreas and ovaries, but only Vtg2 is expressed in the hepatopancreas of M. ensis [14]. Recently, some studies have reported the dual expression (in the hepatopancreas and ovaries) of Vtgs in species such as M. nipponensis [48], P. clarkii [29], and Scylla paramamosain [49].…”
Section: Discussionmentioning
confidence: 99%
“…Vtg1 is expressed primarily in the hepatopancreas and ovaries, but only Vtg2 is expressed in the hepatopancreas of M. ensis [14]. Recently, some studies have reported the dual expression (in the hepatopancreas and ovaries) of Vtgs in species such as M. nipponensis [48], P. clarkii [29], and Scylla paramamosain [49].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatopancreas transcriptomes of 5 ovary stages were compared to gain new insights into the role of the hepatopancreas in ovarian maturation in M. nipponense . Changes in proteins identified in hepatopancreas will provide further information for functional investigations of the molecular regulatory mechanisms involved crustaceans’ sexual maturation [ 22 ]. In present study, a TMT-based proteomics analysis was used to identify key proteins and pathways during ovarian development of M. nipponense .…”
Section: Discussionmentioning
confidence: 99%
“…ASM1510439v1, BioProjects: PRJNA646023; accession No. SAMN27687877–SAMN27687891, Bioproject PRJNA830321) [ 22 , 24 ]. The proteins whose quantitation were significantly different in the HE-I versus HE-II, HE-II versus HE-III, HE-III versus HE-IV, and HE-IV versus HE-V groups ( p < 0.05 and FC < 0.83 or fold change FC > 1.2) were defined as DEPs (differentially expressed proteins).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hepatopancreas of E. sinensis is not only an edible tissue but also serves multiple physiological functions. It is involved in digestion, absorption, and storage of nutrients, particularly during molting [2] and gonadal maturation [3]. Additionally, it plays a role in detoxification and metabolic regulation.…”
Section: Introductionmentioning
confidence: 99%